(untitled) (Global Journal of Human-Social Science, 2016)
Children are the pillars of the future of every society Thus we need to research all aspects related to them as what they are today is what they will be tomorrow For any child labor study to be of any essence it must be understood as part and parcel of the societal interaction in which children are the principal actors in the different stages Essentially child labor study cannot be separated from the human family Data on child labour are very scarce particularly in The Gambia and it is often difficult to measure the largely hidden work of children The ILO has recently designed a new approach which has been piloted in four countries including developing nations and the results used to generate global estimates At present the worldwide record suggests that the estimate of children involved in child labour ranges from 300-400 million which is approximately 4 to 5 of 2 8 billion economically active persons